Pengaruh Hydraulic Retention Time pada Proses Aklimatisasi Reaktor Nitrifikasi Biofilter dari Olahan Limbah Cair Industri Tahu - Fatimah; Turmuzi, Muhammad; Yanqoritha, Nyimas (Jurnal Teknik Kimia USU, 2025)
The characteristics of tofu wastewater in Polonia-Medan contain a high organic load and an acidity degree of between 4-5 so it needs to be treated appropriately. The initial processing technique has been carried out anaerobically, but the NH3-N content is still high so it is necessary to carry out a nitrification process. Biofilters are widely used as a medium for the growth of microorganisms in waste processing.  Bio balls as a medium for the growth of microorganisms have been previously carried out in anaerobic processing of tofu wastewater. This bio ball biofilter is capable of providing optimal growth of microorganisms, so this research also uses bio balls as biofilter media.  Aerobic process in the biofilter nitrification reactor with variations in hydraulic retention time (HRT) of 24, 12, 6 hours and substrate concentrations of 50% and 100% for the acclimatization process. Acclimatization shows that HRT influences the acclimatization process to variations in substrate concentration. The highest removal process results were at 24 hour HRT, 100% substrate concentration, which resulted in NH3-N removal of 86.95%, COD 77.97% and nitrate production of 103.25 mg/L.